Análise geomorfológica do carste da área de proteção ambiental de São Desidério - BA - Dantas, Robson Braga (Universidade Federal do Tocantins, 2017)
The Conservation units (UCs) has the purpose to contribute to the environmental sustainability, thus, this research aimed to analyze the geomorphology of the APA - Environmental Protection Area in the city of São Desiderio-BA. For such, the structural and morpho sculptural aspects of the geomorphological cartography were analyzed, starting from the first to the fifth taxon, through cartographic and morphometric analyzes, assisting to the basis of the study on karstic elements and analysis of environmental degradation factors. The cartographic analysis of the maps were done through theoretical studies, field woril and georeferencing of the chart of Angical - BA, in the scale 1: 100,000, (SD.23-X-A-I). The laboratorial study was carried out using the QGIS 2.16.1 software, In where the, a geographic and cartographic database were organized, using vector files extracted from IBGE institute; SRTM images with 30m resolution, downloaded from TOPODATA / INPE; Images LANDSAT 08 with the R3G4B5 color composition, referring to the orbit 220 / point 68 and vector files extracted from the database of CPRM and EMBRAPA. At the same time, maps of morphometric nature were developed such as digital elevation model, hypsometry, types of terrain forms, shaded relief, topographic profiles were generated with emphasis on the study of the characteristics of the types of slopes and density drainage. The analysis of the karst elements were taken as a parameter from the 3rd, 4th and 5th taxon, through the free walring method according to the criteria of observation of the landscape and study of the surveyed area through cartographic documents and subsequent physical and geographic description at laboratory and office as well with GIS and on-site assistance with GPS and Camera. This analysis was developed through a punctual and qualitative approach, resulting in a geomorphological outline of the area in the 1: 100,000 scale; as well as an exploratory map of karst phenomena in the 1: 100,000 scale. Finally, it were identified factors of environmental degradation, related to water supply in swallow sinks, resurgences, karst springs and degradation of karstic massifs made by explosive detonations. The results confirm that the lack of a UC Management Plan, as well as a lack of scientific studies on the karstic morphology and its fragility, contributng to the fact that the studied landscape, despite composing an immeasurable natural potential, is clearly vulnerable to the interference of an anthropic nature.